The Impact of Student Aid Eligibility on Higher Education Applications - Camille Remigereau; Clara Schäper (CESifo GmbH, 2024)
This study examines how student aid eligibility influences application decisions to higher education using administrative data from the French national centralized platform. We employ a difference-in-differences approach following a change in the income thresholds for aid eligibility. We find that, on average, the financial aid reform did not affect application decisions for all students, but it impacted students differently based on gender and academic performance. High-performing male students showed the strongest reaction, shifting their first-ranked application from non-selective long-term universities to selective long-term programs. On average, female students, regardless of performance, did not show a systematic response to changes in financial aid eligibility. We provide suggestive evidence that female students were more certain in their application choices. Analyzing survey data on students' financial resources, we find that male students face stronger financial constraints than female students when attending long-term selective programs.
Keywords: I22; I23; I24; I38; J16; 330; education; inequality; financial aid; gender